Some Notes on Consumers' Rights in Times of Natural Disasters - Fuentes Véliz, Juan Andrés (2015)
These comments have the objective of opening discussion regarding intervention of the State in the economy, regulating prices in times of natural disasters due to the sudden increase of the demand by consumers and consequent economic exploitation by some providers. Taking the chilean case as example, the authors raise certain legislative amendments to avoid that certain providers take improper advantage of consumers in such dramatic times.